The long and short of doubling down: polyploidy, epigenetics, and the temporal dynamics of genome fractionation. (April 2018) - Wendel, Jonathan F; Lisch, Damon; Hu, Guanjing; Mason, Annaliese S
Abstract : We consider the rapidly advancing discipline of plant evolutionary genomics, with a focus on the evolution of polyploid genomes. In many lineages, polyploidy is followed by 'biased fractionation', the unequal loss of genes from ancestral progenitor genomes. Mechanistically, it has been proposed that biased fractionation results from changes in the epigenetic landscape near genes, likely mediated by transposable elements. These epigenetic changes result in unequal gene expression between duplicates, establishing differential fitness that leads to biased gene loss with respect to ancestral genomes. We propose a unifying conceptual framework and a set of testable hypotheses based on this model, relating genome size, the proximity of transposable elements to genes, epigenetic reprogramming, chromatin accessibility, and gene expression.